Klebsiella Pneumoniae Communiy-Acquired Pneumonia in a Trisomic at Omar Bongo Ondimba's Army Instruction Hospital (HIA OBO) - D Mounguengui; JM Mandji Lawson; H Birinda; M Ondounda; S Olivera; UD Kombila; LD Ibinga; JB Boguikouma (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2016)
Kp community-acquired pneumonia is rarely encountered. Its prevalence is higher in Asia, where a higher strain virulence was demonstrated [1,2]. It's a pyo-pneumothorax, which usually occurs on debilitated or  immuno-compromised patients. It is a severe disease associated with high mortality. Here, we report the observation of a Kp community-acquired pneumonia occurring in a genetic disorder context.